Cloning and charaterisation of the Thyrotrophin-releasing hormone receptor and Gonadotrophin-relasing hormone receptor from chicken pituitary gland - Sun, Yuh-Man (Division of Chemical Pathology, 2018)
The hypothalamic hormones, thyrotrophin-releasing hormone (TRH) and gonadotrophin-releasing hormone (GnRH), play pivotal roles in the growth and sexual maturation of chickens. In chickens, TRH regulates the release and synthesis of thyrotrophin (TSH) and also acts as a growth hormone-releasing factor. GnRH stimulates the release and synthesis of gonadotrophins (LH and FSH). TRH and GnRH are released and stored in the median eminence, and both hormones are transported into the pituitary gland via the hypophysial portal circulation. TRH and GnRH exert their physiological functions by binding to their specific receptors (TRH receptor and GnRH receptor, respectively) on the surface of cells in the pituitary gland. The activated receptors couple to guanine nucleotide-binding regulatory proteins (G proteins), Gq and/or G11, which in turn triggers the secondary messenger [1,2- diacylglycerol (DAG) and inositoltrisphosphate (IP3)] signalling cascade. The signalling generates the physiological effects of the hormones. The TRH-R and GnRH-R are members of G-protein coupled receptor (GPCR) family. The objective of this thesis was to clone and characterise the chicken TRH and GnRH receptors as useful tools for investigating the regulatory roles of TRH and GnRH receptors in the growth and sexual maturation of chickens. In addition, sequence information of the receptors would potentially assist in elucidating the binding sites and the molecular nature of the processes involved in receptor activation.